Effect of Multifocal Intraocular Lens on Contrast Sensitivity in Primary Angle-Closure Patients - Kitnarong, Naris; Dagvadorj, Dovchinjamts (Siriraj Medical Journal, 2023)
Objective: To study the effect of multifocal intraocular lens (MIOL) implantation on contrast sensitivity (CS) compared to monofocal intraocular lens (mIOL) in primary angle-closure (PAC) or primary angle-closure glaucoma (PACG) patients. Materials and Methods: This prospective study included patients with PAC or PACG and visually significant cataract. Phacoemulsification with MIOL or mIOL (patient preference) was performed. Collected data included best-corrected distant visual acuity (BCVA), intraocular pressure (IOP), anterior chamber depth (ACD), and contrast sensitivity (CS) measured at spatial frequency 1.5, 3.0, 6.0, 12.0, and 18.0 cycles per degree (CPD) preoperatively, and at 2-6 months postoperatively. Preoperative and postoperative parameters were then compared. Results: Of the 45 eyes from 35 patients that were enrolled, 33 eyes (15 PAC, 18 PACG) from 26 patients completed the study. Fourteen eyes (11 patients) received diffractive MIOL, and 19 eyes (15 patients) received aspheric mIOL. Preoperative CS was not significantly different between groups. Postoperatively, BCVA, and CS at each spatial frequency were significantly improved in both groups (all p<0.001). Mean postoperative CS at spatial frequency 1.5, 3.0, 6.0, 12.0, and 18.0 CPD was 28.03, 42.63, 44.84, 10.82, and 2.86 in the MIOL group, and 29.55, 49.63, 46.20, 16.83, and 7.09 in the mIOL group, both respectively. Postoperative CS was not significant different between groups at any spatial frequencies. IOP was decreased (p=0.001) and ACD increased (p<0.001) postoperatively in both groups. Conclusion: No significant difference in visual acuity or contrast sensitivity was observed between MIOL and mIOL after cataract removal in patients with PAC/PACG.